The bad daughter : a novel - Fielding, Joy (Ballantine Books, 2018)
"A hostile relationship with her sister and a complicated past with her father's second wife have kept Robin estranged from her family for many years. But when her father's new family is attacked in their house, with her father, his wife, and young daughter in critical condition in the hospital, she returns home to await their fate and hopefully mend fences. It looks like a random robbery gone awry, but as Robin spends more time with her family members, she learns they all had their secrets -- and one of those secrets may have put them all in horrible danger"--
Keywords: Family secrets -- Fiction; FICTION / Suspense; FICTION / Mystery & Detective / Women Sleuths; FICTION / Family Life; Mystery fiction; Suspense fiction